European experience in assessing the potential of innovative consulting services - Levishchenko, Olena; Dziuba, Oksana; Lavryk, Halyna; Zeliska, Antonina; Riabenko, Volodymyr (My University, 2023)
Інноваційні консалтингові послуги в різних секторах економіки ЄС популярні завдяки потенціалу компаній залучати приватні та державні фінансові ресурси. Метою даної статті було дослідження впровадження інноваційних консалтингових послуг для оцінки їх потенціалу. Методологія дослідження базується на статистичному аналізі системи показників інноваційних консалтингових послуг та кореляційному аналізі впливу на діяльність фірм ЄС. Результати показують, що найпоширенішою формою інноваційного консультування є саморозвиток, вдосконалення продукту, процесу, пошук клієнтів, доступ до нових сегментів споживачів тощо. Залучення консалтингових організацій до розробки інноваційних продуктів здійснюють 40% компаній, а впровадження інформаційно-комунікаційних технологій та оновлення бізнес-процесів є найпопулярнішим видом консалтингу в ЄС

Innovative consulting services in various sectors of the EU economy are popular due to the potential of companies to attract private and public financial resources. The purpose of this article was to study the implementation of innovative consulting services to assess their potential. The research methodology is based on a statistical analysis of the system of indicators of innovative consulting services and a correlation analysis of the impact on the activities of EU firms. The results show that the most common form of innovation consulting are self-development, product improvement, process, customer search, access to new customer segments, etc. Involvement of consulting organizations in the development of innovative products is carried out by 40% of companies, and the introduction of information and communication technologies and business process updates is the most popular type of consulting in the EU
Keywords: consulting services; консалтингові послуги; business model; бізнес-модель; кафедра економіки і права